Conservación de patrimonios culturales y su impacto en el desarrollo turístico del cantón Quevedo, año 2021 - España Acosta, Bricey Brigitte (2021)
The following work was prepared in the Quevedo canton of the Los Ríos province in order to know what is the impact of cultural heritage with the tourist development that exists in the Quevedo canton belonging to the Los Ríos province. Its objective is to determine the appropriate skills to reach the conservation of cultural heritages and their impact on tourism development through research in the city so that the Quevedo canton is recognized touristically that will help us in a few words to see that relationship and the set of how the cultural heritage of the city works. Quevedo city with tourism development. For the elaboration, three specific objectives were carried out, the first one is to analyze the tourist environment of the city of Quevedo.